PENGARUH DISIPLIN, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi pada Perum Perhutani KBM Komersial Kayu 1 Jawa Tegah) - Endang Pujowati, 0725020047 (Students Journal of Economic and Management, 2015)
This study aimed to analyze the influence of dicipline, motivation, and job satisfaction with employee performance on perum perhutani kbm komersial kayu 1 jawa tengah. The method used in sample collection in this study was purposive sampling. Instrument tests used are validity and reliability test, with the criteria of KMO > 0.5, Loading Factor > 0.4 and Cronbach alpha > 0.7, while the model test used is Adj-R2 (coefficient of determination) and F-test (Goodness of Fit). Hypothesis test in this study is regression analysis using the t-test. Hypothesis testing is using t-value of frequency distribution at significance level (Î±) of 5%. Based on the results, the study can be summarized as follows: (1) dicipline has positive significant influence on employee performance, (2) motivation has positive significant influence on employee performance, (3) job satisfaction has positive significant influence on employee performance. Keywords: dicipline, motivation, and job satisfaction with employee performance.